Determination of the electron affinity of astatine. Issue 13 (January 2020) - Leimbach, D; Rothe, S; Sundberg, J; Hanstorp, D; ,
Synopsis: Astatine is a promising candidate for targeted alpha therapy in nuclear medicine. However, due to its scarce nature, some of its fundamental properties that determine its chemical characteristics such as the electron affinity, the binding erergy of the additional electron in a negative ion, are still unknown. Here we present the method and results of the first measurement of the electron affinity of astatine, performed with the Gothenburg ANion Detector for Affinity measurements by Laser PHotodetachment (GANDALPH) at CERN-ISOLDE.